2015
DOI: 10.1038/srep11561
|View full text |Cite
|
Sign up to set email alerts
|

Revealing patterns of local species richness along environmental gradients with a novel network tool

Abstract: How species richness relates to environmental gradients at large extents is commonly investigated aggregating local site data to coarser grains. However, such relationships often change with the grain of analysis, potentially hiding the local signal. Here we show that a novel network technique, the “method of reflections”, could unveil the relationships between species richness and climate without such drawbacks. We introduced a new index related to potential species richness, which revealed large scale patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In particular, Baudena et al (2013) showed that the amount of water transferred through transpiration may change up to 10 % if one considers different vegetation patterns, even with the same biomass density and the same spatial scale. Recent efforts have also been focused on downscaling remote sensing information to simulate subgrid surface heterogeneities (e.g., Peng et al, 2016;Stoy and Quaife, 2015), and to scale up information across scales using network techniques (Baudena et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Baudena et al (2013) showed that the amount of water transferred through transpiration may change up to 10 % if one considers different vegetation patterns, even with the same biomass density and the same spatial scale. Recent efforts have also been focused on downscaling remote sensing information to simulate subgrid surface heterogeneities (e.g., Peng et al, 2016;Stoy and Quaife, 2015), and to scale up information across scales using network techniques (Baudena et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, modeling hydroecological effects of "slower" runoff from a peatland can potentially influence vegetation dynamics of mosses in models including moss dynamics, e.g., Porada et al (2013). The HH model is novel in the physical representation of lateral fluxes of water among hummocks and hollows, but other models representing surface hetero-geneity controls on water table (e.g., Shi et al, 2015) and methane fluxes (e.g., Bohn et al, 2013) display similar effects. Therefore, and because of the process-based nature of the HH model, we are confident in hypothesizing similar results if a Hotspot-like parameterization was to be applied to other models.…”
Section: Methane Emissions For 1976-2005mentioning
confidence: 99%
“…In particular, Baudena et al (2013) showed that the amount of water transferred through transpiration may change up to 10 % if one considers different vegetation patterns, even with the same biomass density and the same spatial scale. Recent efforts have also been focused on downscaling remote sensing information to simulate subgrid surface heterogeneities (e.g., Peng et al, 2016;Stoy and Quaife, 2015), and to scale up information across scales using network techniques (Baudena et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crucial mechanisms behind altitudinal patterns of taxon richness include the combined effects of area, climate, and the mid-domain effect (MDE; McCain 2009 ). Mean annual temperature (MAT) and mean annual precipitation (MAP) could also be responsible for a large part of the variance in plant taxon richness (O’Brien et al 1998 ; Baudena et al 2015 ). The MDE has been proposed as one important determinant for hump-shaped patterns of taxon richness along the altitudinal gradient (Colwell et al 2004 ; Kluge et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%